The Effects of S-Allyl-Cysteine and Cannabidiol on Cerebral and Retinal Neurovascular Integrity and Cognitive Function in Type 2 Diabetes - Majimbi, Maimuna (Curtin University, 2024)
Type 2 diabetes (T2D) induces cognitive dysfunction through neurovascular, inflammatory, and oxidative mechanisms. This thesis explores the therapeutic potential of S-allyl-cysteine (SAC) and cannabidiol (CBD) in mitigating these pathophysiologies, comparing their neuroprotective efficacy against metformin. Utilising the clinically relevant db/db mouse model, it reveals that retinal changes mirror brain pathology and can predict cognitive decline. Dietary provision of SAC and CBD showed significant neuroprotective effects, suggesting promising strategies for managing T2D-related cognitive and retinal complications with natural compounds.